Mini-mental state examination in neurological patients. Issue 5 (May 1984) - Dick, J P; Guiloff, R J; Stewart, A; Blackstock, J; Bielawska, C; Paul, E A; Marsden, C D
Abstract : The Mini-Mental State examination has been found to be a quick and valuable test for simple bedside screening, and for serial assessment of cognitive function in a population of 126 neurological patients. Amongst those with cognitive impairment, there was a close relation between the Mini-Mental State examination and the conventional Weschler Adult Intelligence Scale (WAIS). However, the Mini-Mental test was not a sensitive indicator of focal versus diffuse hemisphere disease. Further refinement in the areas of language and visuo-spatial function may improve its value.